2013
DOI: 10.5539/jas.v6n1p96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Acid Rain on Growth and Yield of Cassava Manihot esculenta (Crantz)

Abstract: Southern Nigeria is a major cassava producing area that has been subjected to air pollution from increasing industrial activities and population explosion in the coastal towns and cities. The level of pollution is not expected to change drastically in the immediate future. Investigations were carried out to study the changes in the morphology, survival, growth and yield of TMS 96/1672 cultivar of cassava Manihot esculenta (Crantz) to simulated acid rain. The plants were exposed to simulated acid rain of pH 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(15 reference statements)
2
5
0
Order By: Relevance
“…Observable morphological changes in this work were; necrosis, chlorosis and leaf deformation and stunted growth. This is in accordance with the work of [19, 28,30,31,32]. Physiological and morphological changes induced by SNAR and SSAR on A. hybridus are of keen interest because this vegetable is grown mainly for its leaves.…”
Section: Discussionsupporting
confidence: 90%
“…Observable morphological changes in this work were; necrosis, chlorosis and leaf deformation and stunted growth. This is in accordance with the work of [19, 28,30,31,32]. Physiological and morphological changes induced by SNAR and SSAR on A. hybridus are of keen interest because this vegetable is grown mainly for its leaves.…”
Section: Discussionsupporting
confidence: 90%
“…Both the area affected by acid rain and the acidity of rainwater are increasing, and the frequency can reach a very high level [ 7 ]. The consequences of acid rain in plants include damage to the cell membrane system and negative impacts on respiration, photosynthesis, and the antioxidative enzyme system [ 8 11 ], and low yields, low germination rates, thin roots, premature abscission, branch dieback, necrosis, and morphological changes have been reported [ 3 , 8 , 12 , 13 ]. In addition, some studies have indicated that acid rain effects on the activities of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) on plant species depend on the pH and duration of the acid rain treatments [ 9 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effects of climate, the acidity of the rainwater, and the farming regime are important causes affecting yield. The negative effects of simulated acid rain on yield are also observed for other crops [83][84][85].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Similarly, for the yield index and yield components of soybean, the lower the pH of the rainwater, the more the soybean yield declines with the quantity and quality of the yield components. The effects of acid rain on the growth and development of crops have been documented in studies on corn [24,86,87], soybean [64,77,88], tomato [83,84], and cassava [85]. The damage by acid rain includes chlorosis, necrosis, stunting, and early senescence [27,84].…”
Section: Conclusion and Discussionmentioning
confidence: 99%